Hypophosphatemia Is More Common and Is Prognostic of Poorer Outcomes in Severe Alcoholic Pancreatitis. Issue 10 (November 2021) - Wagner, Jason; Hernandez-Blanco, Yllen; Yu, Abraham; Garcia-Rodriguez, Victor; Mohajir, Wasay; Goodman, Colin; Farooq, Ahmad
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: The aim of this study was to determine if hypophosphatemia is more common in patients with severe alcohol-induced acute pancreatitis (AAP). Methods: This is a retrospective, single institution, cohort study that analyzed 147 patients admitted to the hospital for AAP. Multivariate logistic regression was used to determine if hypophosphatemia would be related to clinical outcomes of disease severity. Results: Hypophosphatemia was more common in patients with severe AAP at admission; in addition, all patients with severe AAP (100%) eventually developed hypophosphatemia during admission, relative to those with mild (43%) and moderately severe (54%) AAP. The magnitude of the lowest phosphate measurement obtained during admission was lower in patients with severe AAP (mean, 1.5 mg/dL, standard deviation [SD], 0.5 mg/dL) relative to those with mild (mean, 2.6 mg/dL; SD, 0.9 mg/dL) and moderately severe (mean, 2.3 mg/dL; SD, 0.9 mg/dL) AAP ( P < 0.001). Finally, patients who developed hypophosphatemia during admission were more likely to require intensive care unit admission ( P < 0.001), vasopressors ( P = 0.01), or intubation ( P = 0.003). Conclusions: Hypophosphatemia is more common and of greater magnitude in patients admitted to the hospital with severe AAP. In addition, patients with severe AAP who develop hypophosphatemia during admission are more likely to have poorer clinical outcomes.